Peningkatan Sikap Humanis dan Religius pada Masyarakat PRA Kartasura: Aksi Nyata Kegiatan TPA dan Pengajian: Increasing Humanistic and Religious Attitudes in the PRA Kartasura Community: Real Action of TPA and Religious Study Activities - Adela Yanuar Zahrani; Reza Diva Primadani; Amanda Miftahul Janah; Aulia Azzahra; Wahyu Nurfitriani Widodo; Riskya Vernanda Pratama; Syamilah; Ahmad Nurrohim (Litera Academica Publishing, 2025)
The Field Work and Community Service Program (PKL-PP) of Universitas Muhammadiyah Surakarta was carried out at the ‘Aisyiyah Branch Leadership (PRA) Kartasura, focusing on strengthening community da'wah values and women's empowerment. The program aimed to foster humanistic and religious attitudes through direct involvement in community activities. Students actively participated in children’s Qur'anic learning groups (TPA), Sunday morning recitations, and Qur’anic interpretation studies. Initial condition analysis revealed that PRA Kartasura has a strong social network and plays an active role in promoting Islamic values, children's education, and women’s empowerment. However, challenges were found in digital documentation and youth participation. Proposed solutions included the development of an electronic documentation system, training in communication and technology-based management, and mentoring in program implementation. Activities were carried out in stages with participatory methods, starting from observation to implementation. The outcomes demonstrated increased child engagement, enhanced management capacity of organizers, and a more organized recording system. To ensure sustainability, collaboration between youth cadres, the university, and PRA is essential. This PKL program offered a transformative experience for students in strengthening sustainable community-based da'wah.